Effects of Self-Efficacy and Work Motivation on the Performance of Driving Teachers in Elementary Schools of Kupang City, East Nusa Tenggara - Manu, Ferderika Nofriyanti; Wibawa, I Made Citra; Margunayasa, I Gede (Journal of Innovation and Research in Primary Education, 2025)
This study aims to analyze the influence of self-efficacy and work motivation on the performance of Guru Penggerak (Driving Teachers) in elementary schools in Kupang City, East Nusa Tenggara. The background of this research is grounded in the essential role of Guru Penggerak in driving educational transformation, a role that demands high competence, strong work ethic, and a high level of self-confidence in carrying out professional responsibilities.This study employed an ex-post facto design involving N = 69 Guru Penggerak across various elementary schools in Kupang City as respondents. The sample was selected using a cluster sampling technique. Data were collected through questionnaires and analyzed using SPSS version 27.00 with simple and multiple linear regression techniques.The results indicate that self-efficacy significantly affects the performance of Guru Penggerak, with an R-squared value of 12.3%, indicating that self-efficacy contributes 12.3% to performance outcomes. Similarly, work motivation showed an R-squared value of 34.5%, indicating a greater contribution to performance. Furthermore, the simultaneous effect of self-efficacy and work motivation on teacher performance was statistically significant, as indicated by an Fhit= 18.257 and a significance level of 0.001. Thus, the null hypothesis (H₀) was rejected, and the alternative hypothesis (H₁) was accepted.These findings suggest that higher levels of self-efficacy and work motivation lead to better performance among teachers in fulfilling their roles as agents of change in the school environment.